Characterization of Heat, Oxidative, and Acid Stress Responses in Brucella melitensis - Teixeira-Gomes, Ana P. (American Society for Microbiology, 2000)
Brucella melitensis is a facultative intracellular pathogen which is able to survive and replicate within phagocytic cells. Therefore, it has to adapt to a range of different hostile environments. In order to understand the mechanisms of intracellular survival employed by virulent B. melitensis 16M, an initial approach consisting of analysis of the differences in patterns of protein synthesis in response to heat, oxidative, and acid pH stresses by two-dimensional (2-D) polyacrylamide gel electrophoresis was used. Depending on the stress, this involved about 6.4 to 12% of the 676 protein spots detected in 2-D gel electrophoresis. On the basis of N-terminal sequence analysis and database searching, 19 proteins whose level of synthesis was up- or down-regulated by stress conditions were identified. Some of them were previously reported for Brucella, such as BvrR, DnaK, GroEL, and Cu-Zn superoxide dismutase (SOD). Eight other proteins closely matched proteins found in other bacteria: AapJ, alpha-ETF, ClpP, Fe and/or Mn SOD, malate dehydrogenase, IalB, 30S ribosomal protein S1, and pyruvate dehydrogenase E1 component beta subunit. Results indicated that B. melitensis could bring specific regulatory mechanisms into play in response to stress conditions. For example, the ribosome releasing factor in B. melitensis appeared to be a heat shock protein, whereas the ClpP protein, described as a heat shock protein for Escherichia coli, was strongly down-regulated in B. melitensis in response to heat stress. Some of the identified proteins and their potential specific regulation could be required for the adaptation of B. melitensis to environmental stresses encountered in phagocytic cells and possibly for bacterial virulence.